Effects of different white nanomaterials on pH response ability and physicochemical performance of anthocyanin-loaded carboxymethyl cellulose-polyvinyl alcohol films - Yuqian Li; Xue Yang; Yunfei Zou; Huixuan Zhang; Ying Zhou; Qiujin Zhu; Yuanyuan Liu; Zhengcong Wang (Food Chemistry: X)
The anthocyanin-loaded films based on natural polymers as pH-responsive indicator are widely applied in the food preservation. However, the low mechanical strength and storage stability limited their practical application, there is an urgent demand to improve the performance of anthocyanin-loaded films. In order to avoid affecting the color indication of anthocyanins, we explored the effect of eight kinds of white nanomaterials on improving the performance of films. The results revealed that some nanomaterials showed capability in improving the polymer molecular interactions and enhancement in mechanical properties, barrier ability, and antioxidant activity. However, nanomaterials containing Zn was not suitable for anthocyanin-loaded film modification, because it could destroy the pH responsiveness of anthocyanin. The nano Al2O3 could increase the sensitivity of anthocyanin-loaded film in pH-response, which achieved the highest performance score during pork storage. This investigation will provide theoretical support for the development of more optimized pH-responsive anthocyanin-loaded films in the future.